Fostering Engagement and Basic Vocabulary Skills through Mini Booklets in Elementary English Learning - Putri, Oky Adinda; Madjdi, Achmad Hilal (Universitas Muria Kudus, 2025)
Engaging young learners in English language lessons while fostering vocabulary development is a key challenge in elementary education. This study investigates the use of mini booklets, designed with colorful illustrations, as a tool to enhance student engagement and support vocabulary acquisition among first-grade students at SD 1 Margorejo. A qualitative case study approach was employed, involving 12 students as participants. Data were collected through observation sheets and teacher reflection notes to examine how the mini booklets influenced classroom dynamics and learning outcomes. The findings indicate that the use of mini booklets significantly increased students’ enthusiasm and participation during English lessons. Students enjoyed interactive activities, demonstrating improved vocabulary retention and confidence in speaking. This study highlights the effectiveness of creative, student-centered teaching materials in early English education, offering practical recommendations for educators aiming to improve engagement and learning outcomes in similar contexts.